A new species of bent-toed gecko (Cyrtodactylus: Gekkonidae) from Seram Island, Indonesia - Oliver, Paul; Edgar, Paul; _, Mumpuni; Iskandar, Djoko T.; Lilley, Ron (Zootaxa, 2009)
A new species of Cyrtodacylus is described from the island of Seram, Maluku Province, Indonesia. Cyrtodactylus nuaulu sp. nov. can be distinguished from other described Cyrtodactylus by the combination of moderate size, dorsal colouration consisting of relatively few large dark brown blotches, presence of a precloacal groove and whorls of dentate tubercles extending the length of the tail. The new species is the fourth reptile currently known only from Seram and surrounding islands, and the herpetofauna of this area appears to include a small but biogeographically significant endemic component.